A Peircean approach to pictorial documents - Jappy, Tony (Public Journal of Semiotics, 2011)
The paper summarizes six chapters of a book introducing Peircean visual semiotics to non-specialists. The book has an epistemological bent, and is intended as an empiricist response to Saussurean rationalism, locked away as it is in the universe of Thirdness. Inevitably, in reducing two hundred and thirty pages to twenty-four, the paper has been shorn of the majority of the original examples, quotations and summaries, the relations between the various chapters (here sections) are not developed in detail and the general presentation is perforce allusive: for example, the dynamic object, surely one of Peirce’s most potent yet least understood concepts, has been simplified in what is, after all, an introductory text; similarly, acquaintance with his system of categories has largely been taken for granted. Finally, Simonides of Ceos’ epigram stating that a poem is a talking painting and a painting a mute poem gives the book its title and a major leitmotiv, namely the way we obtain information from pictorial documents.